Comparison of homogeneous and heterogeneous catalysis for synthesis of biodiesel from Madhuca indica oil] [Uporedno proučavanje sinteze biodizela iz Madhuca indica homogenom I heterogenom katalizom - Singh, B.; Bux, F.; Sharma, Y.C. (My University, 2011)
Biodiesel was developed by transesterification of Madhuca indica oil by homogeneous and heterogeneous catalysis. KOH and CaO were taken as homogeneous and heterogeneous catalysts, respectively. It was found that the homogeneous catalyst (KOH) took 1.0 h of reaction time, 6:1 methanol to oil molar ratio, 0.75 mass% of catalyst amount, 55±0.5 °.C reaction temperature for completion of the reaction. The heterogeneous catalyst (CaO) was found to give optimum yield in 2.5 h of reaction time at 8:1 methanol to oil molar ratio, 2.5 mass% of catalyst amount, at 65±0.5 °C. A high yield (95-97%) and conversion (>96.5%) was obtained from both the catalysts. CaO was found to leach to some extent in the reactants and a biodiesel conversion of 27-28% was observed as a result of leaching.
Keywords: Biodiesel; CaO; Catalyst; KOH; Madhuca indica